Use of 39Ar and 14C for groundwater dating ... - Loosli, Heinz Hugo; Oeschger, Hans (University of Bern, 1980)
Cosmic-ray produced atmospheric 39Ar activity (T1/2 = 269 yr) has been determined at 0.11 ±0.012 dpm/lt argon. Ice samples from two profiles in Greenland bore holes showed conclusively that 39Ar dating leads to correct ages. Corrections can be made for possible contamination of the samples with ambient air during field extraction and during laboratory processing by measuring 85Kr in the same samples. The following isotopes: 14C, 39Ar, 85Kr, 3H, partly 32Si, 13C, and 18O were investigated in 20 groundwater samples. Unexpectedly large discrepancies between “14C ages” and “39Ar ages” were observed for many of these samples. For example, a horizontal profile of a confined sandstone aquifer in the Franconian Albvorland showed decreasing 39Ar and 14C activities from respectively, 100 percent to 17 percent and 80 percent to 0.3 percent of modern activity, corresponding to elapsed time periods of 700 and >20,000 years, respectively. It seems unlikely that gas exchange through the aquiclude is the cause of this ...